OCCUPATIONAL HEALTH ANALYSIS IN MAMBAK VILLAGE, PAKIS ADJI SUB DISTRICT, JEPARA REGENCY - Musdalifa Mafhatul; Saekhol Bakri; Arwinda Nugraheni; Diah Rahayu Wulandari; Dea Amarilisa; Aras Utami (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Occupational health problems are still high in Indonesia. Mambak village located in Jepara Regency is an industrial area, with most of its people working as factory workers. This study aims to see the condition of occupational health in the village of Mambak, Sub District Pakis Adji, Jepara Regency. This was a descriptive research with cross sectional study design. Data collection was obtained by survey to work places in Mambak village. Research sample was taken by total sampling method. The research questionnaire used a control sheet from Puskesmas Pakis Adji, Regency of Jepara. There were 48 workplaces located in Mambak village, 60.4% of the largest businesses are furniture. workplaces with noise hazards were 87,5% and 100% without noise control. About 45.83% had no first aid infrastructure, all workers did not use a complete Personal Protective Equipment (PPE), Ear cover, clothes, and shoeswere not used. Occupational risk factors was 100%, work-related diseases was 68.75% due to eye irritation and wound. Handling first aid work accident by giving red medication and in rinse water were 50%. Occupational disease in Mambak Village is still high. Work environments are not appropriate and occupational risk factors are still high. Prevention and treatment of occupational health in Mambak village is not compatible.  Keywords: Occupational health, Occupational disease, work related disease, Personal Protective Equipment